Building community engagement and outreach in libraries - Moore Crowe, Kathryn; Hélouvry, Joanne (Advances in library administration and organization ;, 2022)
Libraries seeking to grow or enhance community outreach will welcome Building Community Engagement and Outreach in Libraries to assist them in planning and executing engagement programs. Eight chapters offer a variety of methods and strategies that library managers can employ to broaden and enhance their libraries' community engagement activities.The volume includes both theoretical frameworks and strategic case studies.Readers will learn how to plan and execute successful community engagement programs with tips on providing leadership for working with staff, fostering relationships with community partners and using assessment to plan for future programming. Specific applications of community engagement practices include using data to inform stakeholders, providing health literacy workshops, staff training for community programs, outreach to engage the community with archives, working with underserved communities and diversity training. This is an important addition to the literature on how libraries can work with their communities to provide critical services and resources. Providing valuable insights about the diverse ways that outreach can be accomplished within and through our communities, this volume serves as a significant resource for both library managers, their staff and their partners.